Natural control on insects biodiversity under rehabilitation and regenerated secondary forest canopies, Sarawak, Malaysia - Naim, Andyson Luna; Abdul Rahman, Amirul Azimin; Sapian, Solehuddin; James Gerusu, Geoffery; Empin, George Bala (International Journal of Academic Multidisciplinary Research, 2019)
Generally, Malaysia are still lacking of research regarding insects biodiversity or the insects order itself, except for certain order that were important for agriculture and forestry. The study on insects biodiversity been done at two different forest canopies Rehabilitation Forest and Regenerated Secondary Forest. The insects were captured using four types of methods such as pitfalls trap, light-trap, yellow-pan trap and sweep net. The trap installed within the study area and continuously monitored periodically for a period of 10 weeks.There were 4 insects order recorded in Rehabilitation Forest, come from order of Coleoptera (56%), Homoptera (22%), followed by Hemiptera and Lepidoptera with both order with 11%. With the Shannon-Wiener Index of Diversity (H')= 1.149 with the species evenness = 0.829.